<h3>
Answer: 6</h3>
Mark the locations -6 and 0 on the number line. Note that going from -6 to 0, or vice versa, will take exactly 6 steps. Put another way, the distance between 0 and -6 is 6 units. Absolute value represents distance, so it is never negative.
We say ![|-6| = 6](https://tex.z-dn.net/?f=%7C-6%7C%20%3D%206)
Effectively, all we're doing is removing the negative sign.
I assume you meant to write 5^c = 125. The equivalent logarithmic expression for this would be ㏒₅125=c.
Answer:
x=4
Step-by-step explanation:
<u>Step 1</u>:-
given the lengths of two sides of a right angle are represented by 2x and 3(x+1) and longest side is 17 units.
AB = 2x and BC = 3(x+1) and longest side AC= 17
by using Pythagoras theorem
![AC^2 = AB^2 + BC^2](https://tex.z-dn.net/?f=AC%5E2%20%3D%20AB%5E2%20%2B%20BC%5E2)
<u>step 2:-</u>
The hypotenuse is longest side is AC = 17 units
(17)^2 = 4x^2 +9(X+1)^2
on simplification, we will use formula
![(a + b)^2 = a^2 +2ab+b^2](https://tex.z-dn.net/?f=%28a%20%2B%20b%29%5E2%20%3D%20a%5E2%20%2B2ab%2Bb%5E2)
289 = 4x^2 +9(x^2+2x+1)
![13x^2 +18x-280 = 0](https://tex.z-dn.net/?f=13x%5E2%20%2B18x-280%20%3D%200)
finding factors 70 X 52 = 3640
![13x^2 +70x-52x-280 = 0](https://tex.z-dn.net/?f=13x%5E2%20%2B70x-52x-280%20%3D%200)
![13x^2 -52x+ 70x-280 = 0](https://tex.z-dn.net/?f=13x%5E2%20-52x%2B%2070x-280%20%3D%200)
Taking common , we get
13x(x-4)+70(x-4)=0
x-4=0 and 13x+70=0
x=4 and ![13x =-70](https://tex.z-dn.net/?f=13x%20%3D-70)
x=4 and ![x=\frac{-70}{13}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B-70%7D%7B13%7D)
we can not choose negative value so x value is 4
Final answer:- x = 4
<u>verification:-</u>
<u></u>
<u></u>
289 = 4(4)^2+9(4+1)^2
289 = 64 +9(25)
289=289
Answer:
78.5
Step-by-step explanation:
A=πr^2 is the formula. Since you're using pi as 3.14, 3.14 times 5^2 is 78.5 (5^2 is 25 because 5x5=25)
Answer:
12
Step-by-step explanation:
f(x)=x^+4x+2 First, let's evaluate when x=3, x=4 and x=5.
f(3) = 3²+4(3)+2 = 9 + 12 + 2 = 23
f(4) = 4²+4(4)+2 = 16 + 16 + 2 = 34
f(5) = 5²+4(5)+2 = 25 + 20 + 2 = 47
Now, let's find the rate of change.
34 - 23 = 11
47 - 34 = 13
Finally, the average rate of change.
(11 + 13) / 2 = 12